Enhancement of photoelectrochemical performance of BiFeO3 by Sm3+ doping. Issue 7 (1st April 2023) - Man, Suyao; Leng, Xueyang; Bai, Jinlong; Kan, Sihan; Cui, Yanan; Wang, Jiaxin; Xu, Lingling
Abstract: Bismuth ferrite (BiFeO3 ) holds great potentials in the photoelectrocatalysis due to the advantages of low cost, narrow band gap and good chemical stability. However, the photoelectrochemical performance of BiFeO3 is usually inhibited by the poor charge carrier transport. Here, we report the flame annealing synthesized Sm 3+ doped BiFeO3 photocathodes for efficient hydrogen production. Greatly enhanced water reduction activity was found in doped samples. The Bi0.95 Sm0.05 FeO3 composition exhibited largest photocurrent density of 0.1061 mA cm −2 at 0 V vs. RHE in 0.5 M Na2 SO4, which was 5.6 times higher than that of the pristine BiFeO3 . Mott-Schottky analysis and electrochemical impedance spectra proved that the Bi 3+ substitution increased the charge carrier concentration and facilitated the charge migration. Incident photon-to-electron conversion efficiency (IPCE) value for Bi0.95 Sm0.05 FeO3 film (∼6.39% at 325 nm) was approximately ten times higher than that of undoped sample. The high performance can be ascribed to the rational Sm 3+ doping, which can improve visible light absorption ability, facilitate the charge carrier transport kinetics and hinder the recombination of photogenerated carriers. Our work provides a facile cation doping with rare earth ions to improve the photoelectrochemical performances.